Granular Cell Tumour of The Vulva: A Case Report - Khodeza, SM; Begum, Nahar; Begum, Nishat (Anwer Khan Modern Medical College Journal, 2012)
Vulvar granular cell tumours are uncommon neoplasms of neural origin. The clinical presentations, surgical findings and histology of Granular Cell Tumour (GCT) of the vulva in a 50 year old lady is presented. Although rare, this benign lesion must be considered in the differential diagnosis of the labia majora masses, such as Bartholin,s duct cyst, Lipoma, Papilloma, Hydradenoma and Fibroma. DOI: http://dx.doi.org/10.3329/akmmcj.v3i1.10111 AKMMCJ 2012; 3(1): 28-30